Spectrum occupancy of cognitive radio networks: a queueing analysis using retrial queue. Issue 3 (1st September 2014) - Chang, Woan Sun; Jang, Won Mee
Abstract : The authors apply the preemptive priority queueing analysis to cognitive radio networks. Using the proposed analytical model, the authors can quantify the delay, throughput and spectrum occupancy of cognitive radio networks. Cognitive users' packet arrivals form a retrial queue with a proper choice of the retrial rate. The authors illustrate numerical results of the delay, throughput and spectrum occupancy with respect to retrial rate, spectrum sensing time and primary user's busy rate.